2014
DOI: 10.1371/journal.pone.0111096
|View full text |Cite
|
Sign up to set email alerts
|

One Size Fits All? Standardised Provision of Care for Survivors of Sexual Violence in Conflict and Post-Conflict Areas in the Democratic Republic of Congo

Abstract: BackgroundOutcomes of sexual violence care programmes may vary according to the profile of survivors, type of violence suffered, and local context. Analysis of existing sexual violence care services could lead to their better adaptation to the local contexts. We therefore set out to compare the Médecins Sans Frontières sexual violence programmes in the Democratic Republic of Congo (DRC) in a zone of conflict (Masisi, North Kivu) and post-conflict (Niangara, Haut-Uélé).MethodsA retrospective descriptive cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…A surprisingly high proportion of survivors (28%) were male, comparable with another survey by MSF which showed that 17% of all male refugees underwent sexual attacks in their efforts to leave from Central America [29]. Other facility-based studies in non-migration contexts present lower proportions of male survivors, including in an urban slum in Kenya (8%) and in post-conflict settings such as Liberia (2%) and eastern DRC (3%) [11][12][13]. However, our findings echo other studies in conflict areas of DRC, showing that 24% of adult males had experienced sexual violence at some point of their life [30], and in Lebanon with 20% of survivors being men and boys [31].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A surprisingly high proportion of survivors (28%) were male, comparable with another survey by MSF which showed that 17% of all male refugees underwent sexual attacks in their efforts to leave from Central America [29]. Other facility-based studies in non-migration contexts present lower proportions of male survivors, including in an urban slum in Kenya (8%) and in post-conflict settings such as Liberia (2%) and eastern DRC (3%) [11][12][13]. However, our findings echo other studies in conflict areas of DRC, showing that 24% of adult males had experienced sexual violence at some point of their life [30], and in Lebanon with 20% of survivors being men and boys [31].…”
Section: Discussionsupporting
confidence: 53%
“…A number of studies have focused on sexual violence in unstable contexts; of those, most were conducted in conflict or post-conflict zones [4,[11][12][13]. A more limited number of studies have focused on sexual violence among people in transit (this includes refugees, migrants, and asylum seekers); often in specific contexts, such as among migrants in transit in South and Central America [14][15][16] and among refugee populations during/following conflict [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies have found the success of this programme to be mixed, with poor documentation of its activities, thus further ongoing service evaluation and improvements are required. Other programmes in place include those offered by non‐government organisations, but again these are challenged by low numbers of women presenting to services, as well as loss to follow‐up . Local community initiatives have been shown to have a positive impact on the psychological wellbeing of survivors in certain settings, such as the DRC, suggesting that one size does not necessarily fit all in our response to these crimes .…”
Section: A Summary Of Locations Where Sexual Violence In Conflict Is mentioning
confidence: 99%
“…Other programmes in place include those offered by non‐government organisations, but again these are challenged by low numbers of women presenting to services, as well as loss to follow‐up . Local community initiatives have been shown to have a positive impact on the psychological wellbeing of survivors in certain settings, such as the DRC, suggesting that one size does not necessarily fit all in our response to these crimes . Of course, international action on CRSV is delicately intertwined with political sensitivities, as well as ease of access to the affected population.…”
Section: A Summary Of Locations Where Sexual Violence In Conflict Is mentioning
confidence: 99%
“…The few studies that focus on assistance to survivors that exist (e.g. Bolton 2009;Bosmans 2007;Douma and Hilhorst 2012;Roka et al 2014;Steiner et al 2009) call into question the effectiveness of some of these programmes and highlight the need for further research and critical evaluation. However, there is an acute lack of data that can be used to critically and systematically assess the focus and impact of the programmes designed to assist survivors of sexual violence.…”
Section: Introductionmentioning
confidence: 99%